Self-Reflection Amid Social Spotlight: A Study on Self-Concept and Social Anxiety Among High School Adolescents - Sabrini Mentari Rezeki; Marcell Charmicaell; Putri Riyanti Yolanda; Shellen Velisya; Lia Aristantya Saragih (Psikostudia : Jurnal Psikologi, 2025)
High school adolescents are at a developmental stage vulnerable to social pressure and identity formation, often leading to social anxiety, especially when their self-concept is not yet firmly established. High levels of social anxiety can hinder students' social interaction and emotional development, whereas a positive self-concept is believed to serve as a psychological buffer. This study aims to examine the relationship between self-concept and social anxiety among high school students and to explore the influence of social anxiety dimensions on aspects of self-concept. The research employed a quantitative correlational approach using Pearson Product Moment correlation and partial regression analysis on 120 students of SMA Yos Sudarso Medan selected through proportionate stratified random sampling. The results revealed a significant negative relationship between self-concept and social anxiety. Furthermore, the fear of negative evaluation dimension positively influenced the physiological and psychological aspects of self-concept, while irrational beliefs negatively affected the psychosocial aspect, and high personal standards had a positive effect on the psycho-spiritual aspect of self-concept. The implications of this study highlight the importance of strengthening students’ self-concept as a strategic measure to reduce social anxiety and support character formation and mental health in the school environment.Remaja SMA berada pada tahap perkembangan yang rentan terhadap tekanan sosial dan pencarian jati diri, yang kerap menimbulkan kecemasan sosial terutama ketika konsep diri belum terbentuk dengan kuat. Kecemasan sosial yang tinggi dapat menghambat interaksi sosial dan perkembangan emosional siswa, sementara konsep diri yang positif diyakini mampu menjadi pelindung psikologis. Penelitian ini bertujuan untuk mengetahui hubungan antara konsep diri dengan kecemasan sosial pada siswa SMA serta mengeksplorasi pengaruh dimensi kecemasan sosial terhadap aspek-aspek konsep diri. Metode yang digunakan adalah pendekatan kuantitatif korelasional dengan teknik analisis Pearson Product Moment dan regresi parsial terhadap 120 siswa SMA Yos Sudarso Medan yang dipilih melalui proportionate stratified random sampling. Hasil penelitian menunjukkan adanya hubungan negatif yang signifikan antara konsep diri dan kecemasan sosial. Selain itu, dimensi fear of negative evaluation berpengaruh positif terhadap konsep diri fisiologis dan psikologis, sementara irrational beliefs berpengaruh negatif terhadap konsep diri psiko-sosial, dan high personal standards memiliki pengaruh positif terhadap konsep diri psiko-spiritual. Implikasi dari penelitian ini menegaskan pentingnya penguatan konsep diri siswa sebagai langkah strategis dalam menekan tingkat kecemasan sosial serta mendukung pembentukan karakter dan kesehatan mental remaja di lingkungan sekolah.